Is there a need for social information campaign in area of diabetes? - Paula Jankowska; Ewa Rudnicka-Drożak (Kazimierz Wielki University, 2018)
Introduction Diabetes affect constantly wider group of people around world. Multicenter observational studies performed in Poland predicted diabetes prevalence as 6.7-9.8% and in Lublin region as 4,3% of total population. Diabetes is a diseases to some extent preventable, as constantly arising data confirm that lifestyle has even decisive influence on diabetes development. Thus, knowledge about diabetes and awareness of its risk factors and complications is very important. Individuals who are conscious about modifiable variables increasing the risk of developing diabetes may start to improve their everyday behaviors. Objective The aim of this study was to examine knowledge and awareness of diabetes among Lublin inhabitants. Material and methods There was 92 people included in the study. They were Lublin inhabitants. The analysis was based on questionnaire constructed by the authors. Data was analyzed using descriptive statistics and presented as percentages. The obtained results were also statistically analyzed using the STATISTICA 13 program. The significance of intergroup differences was verified with Pearson chi-square test. Results Analysis of participants answers revealed relatively good level of knowledge on diabetes risk factors and complications. Awareness of treatment strategies, diet of suffering patients and opinions on diabetes severity were also evaluated. Conclusions Participants of the study showed relatively satisfactory level of knowledge on diabetes mellitus. They were aware of many disease risk factors, but smoking and advanced age were rarely considered to raise the probability of diabetes development. Furthermore, they had adequate level of knowledge on diabetes complications, except for ischaemic heart disease. According to results of the study, there is a need for convincing social information campaign to raise constantly an awareness of diabetic risk factors and its consequences.